The genomic landscape of phaeochromocytoma. Issue 1 (2nd February 2015) - Flynn, Aidan; Benn, Diana; Clifton‐Bligh, Roderick; Robinson, Bruce; Trainer, Alison H; James, Paul; Hogg, Annette; Waldeck, Kelly; George, Joshy; Li, Jason; Fox, Stephen B; Gill, Anthony J; et al.
Abstract Phaeochromocytomas (PCCs) and paragangliomas (PGLs) are rare neural crest‐derived tumours originating from adrenal chromaffin cells or extra‐adrenal sympathetic and parasympathetic tissues. More than a third of PCC/PGL cases are associated with heritable syndromes involving 13 or more known genes. These genes have been broadly partitioned into two groups based on pseudo‐hypoxic and receptor tyrosine kinase (RTK) signalling pathways. Many of these genes can also become somatically mutated, although up to one third of sporadic cases have no known genetic driver. Furthermore, little is known of the genes that co‐operate with known driver genes to initiate and drive tumourigenesis. To explore the genomic landscape of PCC/PGL, we applied exome sequencing, high‐density SNP‐array analysis, and RNA sequencing to 36 PCCs and four functional PGL tumours. All tumours displayed low mutation frequency, in contrast to frequent large segmental copy‐number alterations, aneuploidy, and evidence for chromothripsis in one case. Multi‐region sampling of one benign familial PCC tumour provided evidence for the timing of mutations during tumourigenesis and ongoing clonal evolution. Thirty‐one of 40 (77.5%) cases could be explained by germline or somatic mutations or structural alterations affecting known PCC/PGL genes. Deleterious somatic mutations were also identified in known tumour‐suppressor genes associated with genome maintenance and epigenetic modulation. A multitude of other genes were also found mutated that are likely important for normal neuroendocrine cell function. We revisited the gene‐expression subtyping of PCC/PGL by integrating published microarray data with our RNA‐seq data, enabling the identification of six robust gene‐expression subtypes. The majority of cases in our cohort with no identifiable driver mutation were classified into a gene‐expression subtype bearing similarity to MAX mutant PCC/PGL. Our data suggest there are yet unknown PCC/PGL cancer genes that can phenocopy MAX mutant PCC/PGL tumours. This study provides new insight into the molecular diversity and genetic origins of PCC/PGL tumours. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.